DAMPAK PENDIDIKAN DAN PELATIHAN SANTRI SIAP GUNA (SSG) DALAM PEMBENTUKAN KARAKTER BAIK DAN KUAT (BAKU) DI PESANTREN DAARUT TAUHID BANDUNG - Shintya Annisa Ainayah; Novi Widiastuti (IKIP Siliwangi, 2023)
This research is motivated by the existence of an education and training program for Santri Ready to Use (SSG) at the Daarut Tauhid Islamic Boarding School in Bandung which is oriented towards the formation of good and strong characters (BAKU). The purpose of this study is to obtain an overview of the planning, implementation, and impact of the results of the education and training of Ready-to-Use Santri that form good and strong characters (BAKU). The research theory used is the theory of character education, education and training, and the concept of character building in public education. The method used in this study is a descriptive method with a qualitative approach. The research subjects were three people, consisting of coaches, program managers, trainers in Santri Ready to Use (SSG). Data collection techniques using interviews, observation and documentation studies. The findings from this character education and training are 1) Planning, namely the preparation of the program is carried out by the SSG Daarut Tauhid program manager, so that there is synergy in determining the program to be implemented. 2) The implementation of character education and training is carried out using a strategy based on mosque activities and field practice. 3) The results of this education and training of good characters which include sincerity, honesty, humility, and strong character including courage, discipline, toughness, has met the needs of the training participants and has been implemented in daily life. The conclusion of this research is that the impact of education and training of ready-to-use students in the formation of standard characters has6been successful and the participants are able to apply these standard character values.